Prototype User Interface Mobile App E-Learning - Henderi Henderi; Praditya Aliftiar; Alwan Hibatullah (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
Information technology has developed rapidly from time to time. One of the technologies commonly owned by many people today is smartphones with the Android and IOS platforms. By knowing this factor, mobile developers compete with each other to design applications with attractive user interfaces so that users are interested in using them. At this stage in mobile application development, starting from designing a user interface prototype. This stage aims to visualize user needs, improve user experience and simplify the coding process by programmers. In this study, researchers applied the prototype method. This research produces a prototype design for the e-learning application user interface which consists of a high fidelity prototype.